Evaluation on perceived service quality on parcel locker delivery service - Ahmad, Siti Azfanizam; Zhafira, Nadia; Abd Rahman, Nurul Izzah (Global Academic Excellence, 2023)
The rise in the number of e-commerce transactions in Indonesia has increased the number of goods to be delivered, which mostly using parcel delivery service. The most favorable parcel delivery alternatives in Indonesia are direct delivery services. Recently, delivery service providers innovated parcel locker service as one of the self-service technologies (SSTs) to self-collect the parcel to increase parcel delivery efficiency. However, this SST service has not been used optimally in Indonesia. To intensify customers’ intention to use the service, service quality evaluation plays an important role to help retain customers and create inﬂow of new customers. The objectives of this study are to identify, evaluate, and prioritize the perceived service quality of parcel locker delivery from a customer perspective using the Bayesian Best-worst method (BWM), which calculates the weight and aggregates the final weights of criteria from all decision-makers (DMs) and Pareto principle. The prioritized service quality are evaluated further to come up with the proposed alternative solutions using the Delphi study. There are in total of four SST quality attributes with three corresponding sub-attributes each, which gives a total of twelve sub-attributes identified. The Bayesian BWM results show that Privacy Security is perceived as the most important service quality in a parcel locker based on customer perspective with the highest optimal weight (0.3562), followed by Convenience (0.2776), Functionality (0.2465), and Enjoyment (0.1198), respectively. Furthermore, there are seven prioritized sub-attributes to be focused on, and initially, eighteen parcel locker specifications were proposed as the alternative solutions in response to those sub-attributes. Based on the results obtained from nine expert users using the Delphi study show that there are a total of fourteen specifications were endorsed. This study evaluates the customer perceived service quality and produces recommendations in the form of alternative solutions for the prioritized service quality.